Germination Ecology of Ivy-Leaved Morning-Glory: an Invasive Weed in Soybean Fields, Iran - SIAHMARGUEE,A. (2020)
ABSTRACT: Ivy-leaved morning-glory (Ipomoea hederacea Jacq.) is an exotic species that is becoming an increasing problem in soybean fields of Golestan province, Iran. Because little information is available on the biology of this weed species in Iran, experiments were conducted to investigate the effects of different factors on seed germination and emergence of Ivy-leaved morning-glory. Maximum germination occurred at constant temperature of 20 oC (82%) and alternating temperature of 15/25 oC (94%). Germination was reduced with increasing salinity and drought stresses. Sodium chloride concentration and osmotic potential that inhibited 50% maximum germination were -1.64 and -1.03 MPa, respectively. Acidity was a limiting factor for the germination, due to inhibiting effect of alkaline conditions on germination. However, the results showed that high temperature pretreatment >100 oC decreased seed germination. Germination decreased from 82 to 3% as temperature increased from 100 to 130 oC. There was no significant difference between seedling emergence in burial depths of 1 to 10 cm, but emergence reduced with increasing burial depth from 10 to 14 cm, and no seedling was emerged from a depth of 15 cm. The results of the flooding experiment also revealed that the seeds of this species are sensitive to this stress, so that emergence was 9% after 3 d flooding.